2016
DOI: 10.17559/tv-20140922220409
|View full text |Cite
|
Sign up to set email alerts
|

A Scrumban integrated gamification approach to guide software process improvement: a Turkish case study

Abstract: Original scientific article In recent years, there has been an increasing interest in tailoring agile development methodologies by combining different agile practices. The adoption of such a balancing approach requires a systematic customization of best practices among agile methodologies. This paper presents an empirical case study for adopting a hybrid Scrumban methodology with an integrated gamification approach, which was conducted in the context of a small-medium enterprise (SME). First, we conducted a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
(16 reference statements)
0
5
0
1
Order By: Relevance
“…Yilmaz and O'Connor (2016) identified that gamification in the form of user stories and badges provided a sense of progression and even fun for participants in software development. This led to increases in cooperation and task completion at the individual and organizational levels (Yilmaz & O'Connor, 2016). Similarly, Khanzadi et al (2018) tested the effects of a gamified pay-for-performance system for lean design management of construction teams and found that gamification effectively enhanced team efficiency by removing the non-value-adding tasks from the design processes and motivating design engineers.…”
Section: Gamification For Task Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Yilmaz and O'Connor (2016) identified that gamification in the form of user stories and badges provided a sense of progression and even fun for participants in software development. This led to increases in cooperation and task completion at the individual and organizational levels (Yilmaz & O'Connor, 2016). Similarly, Khanzadi et al (2018) tested the effects of a gamified pay-for-performance system for lean design management of construction teams and found that gamification effectively enhanced team efficiency by removing the non-value-adding tasks from the design processes and motivating design engineers.…”
Section: Gamification For Task Performancementioning
confidence: 99%
“…While collection of data at the time of service was suggested as a helpful method to get inputs on the effectiveness of employee training, information on data retention over time should also be considered (Miller et al, 2018). Many researchers suggested a larger sample size to ensure more representativeness and for obtaining statistically significant outcomes (Liu et al, 2018;Mitchell et al, 2020;Scheiner, 2015;Yilmaz & O'Connor, 2016).…”
Section: Sustaining Gamificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Alqudah and Razali [18] suggested that scaled Agile methodologies are essential for the large scaled software project development where large team with requirement specific expertise are essential to overcome the limitations [43] of existing agile methodologies like XP, DSDM, Scrum and Kanban. Yilmaz and O'Connor [23] performed a cross section survey in technical research and development organizations for the gamification project, as part of their empirical case study in 2016, to get an opinion of technology experts about adoption of a hybrid software development methodology -Scrumban and they carried out as a result that Scrumban helps in improving productivity of individual and organization. Salah et al [9] recommended a hybrid form of agile based frameworks in 2017, to overcome the challenges with Scrum like budget estimation, project delivery and goal achievement.…”
Section: Empirical Analysismentioning
confidence: 99%
“…System development life cycle is constructed with the various phases to be used in order to develop a good quality system [1][2][3]. Requirement elicitation is an important phase of system development life cycle, since it is the phase where the requirements are elicited and extracted from the stakeholders [4][5][6] Implementing and developing all the elicited requirements is extremely difficult with limited resources such as budget constraints, short schedule, and limited staff power [7,8].…”
Section: Introductionmentioning
confidence: 99%